2014
DOI: 10.11648/j.ajbio.20140204.18
|View full text |Cite
|
Sign up to set email alerts
|

Phycoremediation of Pb+2, Cd+2, Cu+2, and Cr+3 by Spirulina platensis (Gomont) Geitler

Abstract: Phycoremediation is an application of algae for remediate environmental pollution by reducing or eliminating toxicity of such components in waste water. One of environmental problem in Indonesia is heavy metals pollution. Heavy metals are required by microalgae in a trace concentration, but in a high concentration heavy metals are toxic. Spirulina platensis is a microalgae belong to Cyanobacteria that has been used as a single cell protein, feed fish, and supplement. Many researchs on S. platensis had been don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
0
10
0
2
Order By: Relevance
“…The active sites binding was also confirmed in other bio-adsorbent such as banana peel Hossain.al [31], macroalgae [32] and mushroom [33]. The adsorption of metals are also related to biomass which provides more availability of active sites for binding of ions and this was proved by Huang and Lin [34], Putri et al [35] and Soeprobowati & Hariyati [9]. The studies showed decreasing biomass at the longer incubation time, after rapid growth at first period of incubation.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…The active sites binding was also confirmed in other bio-adsorbent such as banana peel Hossain.al [31], macroalgae [32] and mushroom [33]. The adsorption of metals are also related to biomass which provides more availability of active sites for binding of ions and this was proved by Huang and Lin [34], Putri et al [35] and Soeprobowati & Hariyati [9]. The studies showed decreasing biomass at the longer incubation time, after rapid growth at first period of incubation.…”
Section: Resultsmentioning
confidence: 66%
“…This is the major issue in Indonesia was reported the serious effects to organisms [7], [8]. Heavy metals like cadmium and lead are very toxic even at low concentrations [9], [10]. Due to the toxic effects to organisms, cadmium and lead need to be removed before they accumulate in the environment and finally will pass into the human food chain which could result in health problems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 10 shows that the concentration of Cd is above the tolerable limit specified by World Health Organization (WHO) and Food and Agriculture Organization (FAO) (0.003 mg/L and 0.01 mg/L, respectively) [73,74]. Potential sources of cadmium in the Dhaleshwari River include batteries, pigments, and plating businesses [37,70]. The highest Cr concentration observed at D-1 (0.92 mg/L), which may be caused by effluents from the Savar tannery industries, is higher than WHO allowable limit (0.05 mg/L).…”
Section: Comparative Assessment Of Heavy Metal Contaminationmentioning
confidence: 99%
“…The Association of metals in sediments of various geological stages has a significant impact on the cumulative behavior of heavy metals in aquatic environments [36]. In predicting potential pollution, flexibility, and bioavailability, geochemical speciation and metal distribution in the given chemical fractions are generally used [36][37][38][39]. River water polluted with heavy metals such as cadmium (Cd), chromium (Cr), zinc (Zn), and nickel (Ni) can damage crops such as vegetables and rice [40][41][42][43][44].…”
mentioning
confidence: 99%